Pengaruh Rasio Likuiditas, Leverage, Rasio Aktivitas, dan Firm Size Terhadap Earning Per Share (EPS) pada Perusahaan Sektor Customer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Fenny; Budi Kurniawan (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the influence of Liquidity, Leverage, Activity and Firm Size on Earning Per share. The population in this study is companies in customer goods industry listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The data used in this study is secondary data obtained from the Indonesia Stock Exchange web. The number of samples used as many as 34 companies with the number of observations as many as 102 through purposive sampling. The data analysis method used is multiple regression by using SPSS version 26. The results showed that partially Current Ratio, Debt to Equity Ratio has a positive and significant effect on Earning per Share. Firm Size has no effect on Earning per Share. Results simultaneously show Liquidity, Leverage, Activity and Firm Size simultaneously affect Earning Per Share.